The Impact of Zoning Policy Implementation and the Education Production Function in Improving the Quality of Senior High School Education - Nurfakihiswara, Iman; Yudhistira, Muhammad Halley; Mauleny, Ariesy Tri (Monas: Jurnal Inovasi Aparatur, 2024)
This study aims to examine the inequality in the quality of education in 117 public high schools in DKI Jakarta, as well as the effect of implementing the PPDB zoning policy in improving the quality of school education. Utilizing a panel dataset of school units processed through quantitative analysis and Fixed-Effect (FE) econometric regression estimation, this study analyzes the Education Production Function. The research also investigates educational quality disparities based on Gini coefficients with the National Examination scores as indicators. The results of the study found that inequality between schools in DKI Jakarta was at a low level. Furthermore, it is found that the UN participant-to-teacher ratio, teacher education and experience, as well as the implementation of the zoning policy for student admission (PPDB), have an impact on improving school UN score achievements. In the future, school excellence will be distributed divergently.